Pengaruh Perhatian Orang Tua Terhadap Pembentukan Karakter Islami Pada Pondok Pesantren Modern Muhammadiyah Kwala Madu Langkat - Adi Hartono; Putri Apriani Pasaribu; Celline Efrilia; Enni Halimatussa’diyah Pakpahan (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The context of this research is basically a current phenomenon where a child's character is very far from the corridors of religious law, of course due to several factors, therefore parents play a very important role in the formation of a child's character. The family is the smallest community in a child's life. Many things that a child learns from childhood from his family. Especially for Mama and Papa, parents have a big role in shaping the character of children. The role of parents in educating children in the household is very important because it is in the household that a child first receives guidance and education from his parents. The purpose of this study was to determine the effect of parental attention on the formation of Islamic character with the method used, namely the functional correlation quantitative approach. The data collection technique uses a questionnaire /questionnaire with analysis using simple linear regression statistical analysis. The implementation of the influence of parents' attention on the formation of Islamic character in santi/students at the modern Muhammadiyah Islamic boarding school kwala madu Langkat brings the direction of the influence of the X variable on the Y variable which is positive. The result of the significance of Ha is accepted and Ho is rejected. This test can be proven by the regression equation Y = 56.469 + 0.461X with a large effect that the variable Parents' Attention to the Formation of the Islamic Character of Islamic Students is 31.03% while the remaining 68.97% is influenced by other factors. Keywords: Islamic Character, Attention Parents.